2021
DOI: 10.1016/j.psychres.2021.113902
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and psychiatric admissions: An observational study of the first six months of lockdown in Melbourne

Abstract: Research on the effect of a prolonged lockdown on inpatient admissions is limited. In this background, this study was planned, and it included patients admitted to inpatient units of a large mental health network in Melbourne during the lockdown (March 16–September 16, 2020) and a similar time period in 2019. The results showed a 12% decrease in admissions. The lockdown period included patients with lower mean age and more patients with never married status, higher education status, students and patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 8 publications
5
20
1
Order By: Relevance
“…As shown in Multimedia Appendix 3 , several studies reported a reduction in face-to-face visits [ 21 , 22 ] and emergency department presentations [ 23 ], with a reduction in the activity of specialized settings, such as electroconvulsive therapy clinics [ 24 - 27 ]. Data on hospitalizations were less clear, with some studies reporting evidence of a reduced number of admissions (eg, [ 28 , 29 ]), others reporting evidence of a rapid increase in admissions soon after the pandemic onset (eg, [ 23 , 30 ]), and still others reporting no differences compared to the same period in the previous year (eg, [ 31 , 32 ]).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Multimedia Appendix 3 , several studies reported a reduction in face-to-face visits [ 21 , 22 ] and emergency department presentations [ 23 ], with a reduction in the activity of specialized settings, such as electroconvulsive therapy clinics [ 24 - 27 ]. Data on hospitalizations were less clear, with some studies reporting evidence of a reduced number of admissions (eg, [ 28 , 29 ]), others reporting evidence of a rapid increase in admissions soon after the pandemic onset (eg, [ 23 , 30 ]), and still others reporting no differences compared to the same period in the previous year (eg, [ 31 , 32 ]).…”
Section: Resultsmentioning
confidence: 99%
“…9 Admissions to four inpatient units across the region reduced by 12% after the onset of the pandemic. 10 Decreased admissions rates were likely related to fear of infection in hospitals, and higher clinical thresholds for admission.…”
Section: Acute Demand During the Pandemicmentioning
confidence: 99%
“… 15 In Melbourne, increases in presentations for psychosis, anxiety or substance use during the 2020 lockdown were matched by decreases in those for mood disorders or suicidal behaviour compared to control periods. 16 , 17 …”
Section: Research Evidencementioning
confidence: 99%